The effectiveness of digital health interventions for the maintenance of physical activity following cardiac rehabilitation: A systematic review and meta-analysis - Alexander Luijk; Sofie Rath Mortensen; Trine Grønbek Hamborg; Graziella Zangger; Jonas Risum Ahler; Jan Christensen; Søren T Skou; Lars Hermann Tang (Digital Health, 2024)
Objective To summarise the effectiveness of digital health maintenance interventions for subjectively and objectively measured physical activity level (PA) and physical function, fitness and health-related quality of life (HRQoL) after completion of phase II cardiac rehabilitation (CR). Methods We conducted a search for studies in MEDLINE, Embase, CENTRAL, and CINAHL (inception to May 2024). Independent reviewers selected and included randomised controlled trials (RCTs) using digital health interventions to maintain PA in patients with cardiovascular disease after phase II CR. Independent reviewers conducted data extraction, assessed the risk of bias using the Cochrane Risk of Bias 2 tool and rated the certainty of evidence using Grading of Recommendations Assessment, Development and Evaluation – registered at PROSPERO: CRD42023396629. Results From 17,455 hits, 20 RCTs with 1801 participants were included. Risk of bias for most studies reporting on PA outcomes was rated as ‘some concerns’. Comparing digital health intervention with minimal intervention/usual care showed no effect of objective PA (standardised mean difference (SMD) 0.85, 95% CI: −0.07 to 1.77) and a small effect of subjective PA (SMD 0.37, 95% CI: 0.05 to 0.69) at the end of intervention both graded as very low certainty of evidence. We found very low certainty of evidence for moderate effects on physical function (SMD 0.63, 95% CI: 0.03 to 1.24), and low certainty of evidence for no effect on physical fitness (SMD 0.19, 95% CI: 0.05 to 0.34) and HRQoL (SMD 0.13, 95% CI: −0.02 to 0.28), I 2 = 0.00%) at the end of intervention. Conclusion Digital health interventions showed a small effect on subjectively measured PA, and no effect on objective PA, physical fitness and HRQoL, but may increase physical function after CR completion. Yet, the certainty of evidence is low and higher quality studies with longer follow-up duration are needed to guide this area further.